PENGARUH STRUKTUR KEPEMILIKAN, CORPORATE GOVERNANCE, DAN UNDERWRITER REPUTATION TERHADAP IPO UNDERPRICING (Studi Empiris Pada Perusahaan Yang IPO di Bursa Efek Indonesia tahun 2006-2014) - Irawan, Puji; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2015)
Underpricing is a phenomenon when the price in the IPO is lower than the secondary market so that issuers can’t maximally to obtaining additional capital from go public. It is often occurs in various countries in the world. In Indonesia from 2006-2014 there are 189 companies and 153 companies or 80,9% companies experienced underpricing. Underpricing not only influenced by financial factors but also non financial factors (board structure an ownership structures).This study aimed to examine the effect of board size, board independence, ownership concentration, institutional ownership, and the underwriters of the IPO underpricing reputation.The research sample as many as 64 companies had an Initial Public Offering (IPO) in Indonesia Stock Exchange in 2006-2014 and experiencing underpricing. The sampling method used in this study is proposive sampling. Technical analysis that used in this study is Ordinary Least Squares Regression (OLS), t statistical test, and classical assumption test including normality test, multicolinearity test, heterocedasticity test, and autocorrelation test.These results indicate that the number of commissioners have a negative and significant effect on underpricing, while the concentration of ownership has a positive and significant effect on underpricing. However, there was no significant effect of the independence of the commissioners, institutional ownership and reputation underwiter the level of underpricing.